Validity index of ultrasonography findings, fine needle aspiration cytology, PSA and DRE in patients suspicious for prostate cancer - Hatami, Hossein; Mohebbi, Mahdi; Tabatabaei Nodoushan, Mohamad Hossein (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: Prompt diagnosis and treatment of prostate cancer is important to improve the prognosis. Hence in this study the role of radiology and FNA were compared for diagnosis of prostate cancer. Materials and Methods: In this correlational-descriptive comparative study, 100 patients suspected to have prostate cancer were assessed. The results of FNA and radiology were compared. Results: The final diagnosis was BPH in 68%, prostatitis in 24% and malignancy in 8%. Sensitivity and specificity of fine needle aspiration (FNA) were calculated respectively 100% and 90.22%, for ultrasonography 100% and 69.57%, for digital rectal exam (DRE) 75% and 58.7% finally for prostate serum antigen (PSA) 87% and 55%. Conclusions: In general, we found out FNA has the highest validity index but regarding the invasive nature of the test it is not the primary exam to assess the patients. The high false positive cases found by PSA suggests that it may be a suitable screening test but not a reliable diagnostic one to find the patients with cancer.